Eye Tracking Evaluations of Control Populations and Children with Focal Epilepsy - O'Flaherty, Eileen Louise (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2021)
Eye tracking has emerged as a powerful tool in studying the eye movements of children. Previous eye tracking studies have not examined eye movements of children with focal epilepsy. The aim of this study was to develop a protocol for a remote eye tracker and to build a set of normal control data from healthy adults and children. The study then set out to examine if any differences in eye movements could be detected in children with focal epilepsy when compared with a group of normal controls. This study provides a novel approach to measuring eye movements with an infrared eye tracker in both a hospital and community setting. Evidence is presented which shows that it is possible to differentiate children with focal epilepsy and their peers by use of this remote eye tracking protocol. As a result of these investigations, remote eye tracking will be offered to more patient cohorts within the field of Paediatric Neurology.
APPROVED
Keywords: Paediatric Epilepsy; Eye Tracking; Paediatric Focal Epilepsy; ESES; BECTS; Eye tracking Children